2008
DOI: 10.2320/matertrans.m-mra2008827
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Arsenic and Manganese in Contaminated Groundwater by Permeable Reactive Barriers Using Zero Valent Iron and Sheep Manure

Abstract: A permeable reactive barriers (PRBs) column test was carried out to remove arsenic (As) and manganese (Mn) from groundwater using zero valent iron (ZVI), sheep manure, compost and woodchips as reactive materials. Arsenic was mainly immobilized through sorption and co-precipitation with iron-bearing minerals, and also possibly precipitation as FeAsO 4 . The presence of sulfate-reducing bacteria (SRB) in the inoculated column was suggested by decrease of sulfate concentrations and increase of 34 S in the effluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…It has been reported that various Ca-As precipitates were found to be the main compounds responsible for As immobilization by numerous researchers upon lime treatment (Dutré and Vandecasteele 1996;Dutré and Vandecasteele 1998;Moon et al 2004;Moon et al 2011b). Moreover, Fe-As precipitates which could be responsible for effective As immobilization have been widely reported (Chung et al 2001;Kim et al 2003;Lee 2006;Kumpiene et al 2008;Wilopo et al 2008;Drahota and Filippi 2009). In the case of the Pb immobilization mechanism, Pb immobilization was most probably associated with Ca, Al, Si, and O (Fig. 4b).…”
Section: Sem-edx Analysesmentioning
confidence: 94%
“…It has been reported that various Ca-As precipitates were found to be the main compounds responsible for As immobilization by numerous researchers upon lime treatment (Dutré and Vandecasteele 1996;Dutré and Vandecasteele 1998;Moon et al 2004;Moon et al 2011b). Moreover, Fe-As precipitates which could be responsible for effective As immobilization have been widely reported (Chung et al 2001;Kim et al 2003;Lee 2006;Kumpiene et al 2008;Wilopo et al 2008;Drahota and Filippi 2009). In the case of the Pb immobilization mechanism, Pb immobilization was most probably associated with Ca, Al, Si, and O (Fig. 4b).…”
Section: Sem-edx Analysesmentioning
confidence: 94%
“…Four main mechanisms are reported for the removal process are: (1) contaminant adsorption on Fe 0 surface or at the surface of their corrosion products [24][25][26][27][28][29]; (2) contaminant co-precipitation with metal corrosion products (MCPs) [20,30,31,32], (3) contaminant oxidation within the oxide layer [33,34], and (4) contaminant reduction including catalytic hydrodehalogenation [35][36][37]. The hart fact that oxidation of some contaminants and reduction others were reported challenges the prevailing view considering Fe 0 as a reducing agent as discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…Where Q is the sorbed Hg per unit amount of sorbents (mmol kg −1 ) at the equilibrium, C e is equilibrium concentration of mercury (mmol dm −3 ), and K f and n are constants representing the adsorption capacity and adsorption intensity of the adsorbent, respectively (Wilopo, et al, 2008). The data plotted according to the Freundlich model ( Figure 3) showed good correlation coefficients (Table 1).…”
Section: Resultsmentioning
confidence: 87%